Louis Martin papers - Martin, Louis, 1912-1997.
Correspondence, memoranda, interview and oral history transcripts, speeches, writings, notebooks, reports, newspaper clippings, printed material, and other papers relating chiefly to Martin's service as presidential advisor and civil rights liaison for presidents John F. Kennedy, Lyndon B. Johnson, and Jimmy Carter and to his writings which include articles, newspaper columns, and memoirs. Documents his work in establishing African Americans as a political power within the Democratic Party and encouraging their appointment to policymaking government positions. Includes material relating to Martin's involvement with African American newspapers and to his work as chairman of Calmar Communications.
Correspondents include Ronald Harmon Brown, Jimmy Carter, Sharon Pratt Kelly, Lyndon B. Johnson, Vernon E. Jordan, Martin Luther King, Jr., Walter F. Mondale, Sargent Shriver, Frances M. Voorde, Jack H. Watson, and Phil Wise.
Library of Congress Prints and Photographs Division.
Library of Congress Manuscript Division reference collection.
Civil rights activist, newspaper publisher and columnist, and political advisor. Full name: Louis Emanuel Martin. Died 1997.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown, Ronald Harmon, -- 1941-1996 -- Correspondence; Carter, Jimmy, -- 1924-; Carter, Jimmy, -- 1924- -- Correspondence; Kelly, Sharon Pratt, -- 1944- -- Correspondence; Johnson, Lyndon B. -- 1908-1973; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Jordan, Vernon E. -- 1935- -- Correspondence; Kennedy, John F. -- 1917-1963.; King, Martin Luther, -- Jr., -- 1929-1968 -- Correspondence; Mondale, Walter F., -- 1928- -- Correspondence; Shriver, Sargent, -- 1915-2011 -- Correspondence; Voorde, Frances M. -- Correspondence; Watson, Jack H., -- 1938- -- Correspondence; Wise, Phil -- Correspondence; Calmar Communications; Democratic Party (U.S.); African American newspapers; African American politicians; African Americans -- Civil rights; African Americans -- Politics and government; Civil rights; United States -- Politics and government -- 1945-1989.; Political activists; Presidential advisors; Publishers